Sub-sector analysis. Telecommunication services - Villanueva, Edgar Joseph G. (Animo Repository, 2018)
Telecommunication sub-sector is part of the broader and more prominent services sector of the Philippine Stock Exchange. Services sector deals primarily in the business of retail, transportation services, casinos and gaming, hotel and leisure, information technology, media, and telco. This paper will focus only in one subsector which is the telco. Numerically, out of the 30 publicly listed entities that belongs to the Philippine Stock Exchange Index (PSEi), two entities are tagged under the telco sector. The economy had a mixed performance and sentiments in the third quarter of 2018. Retail sales grew significantly because of the increase in prices brought by the implementation of TRAIN law which significantly impacted the price sensitive consumers in the Philippine Market. Remittances from Overseas Filipino Workers grew tremendously in annual terms, while Government’s infrastructure construction program boosted fixed investment. Consumer’s confidence in the economy and in the current political administration turned adverse and negative because of the ballooning inflation rate starting August of the current year. The increase in prices brought by inflation casted a significant doubt whether the robust consumer spending will be sustainable and will be maintained in the coming months. The noted downside in the Government infrastructure push is an on-going surge in importation of capital goods which caused the trade deficit to grow bigger. These events with the rising prices of goods in the market slows down economic growth. (Focus Economics, 2018) Numerically, Real Gross Domestic Product (GDP) grew by 6% (refer to Exhibit 6), which was generally broadbased because most of the key sectors expanded during the previous quarter. Based on the preliminary results of the Labor Force Survey in April 2018, unemployment rate is at 5.5% which translates to approximately 2.4 million individuals. Most of the unemployed individuals’ demographics were males, with ages ranging from 15-24 years. On the other hand, employment rate declined from 94.7% to 94.5% due to reduction in labor forces. The underemployment rate decreased as well to 17% from 18%. A published article from Bangko Sental ng Pilipinas states that a large part of the underemployment was in the services sector; whose largest chunk comprises the telecommunication sub-sector. (Bangko Sentral ng Pilipinas) Philippine Statistics Authority regularly produces reports and monitors the trend in consumer spending. In one of its report it was mentioned that household consumption growth during the first quarter of 2018 slowed down to 5.6% a year ago and 6.2% from the previous quarter. (PSA , 2018) There is a sustained growth in the Philippine economy as previously discussed. Although higher than the previous year, the headline inflation rate reached 6.4% during the month of August – a rate which is an alltime high for the past 8 years. This rate had been beyond the Government’s inflation-controlled range of 2% to 4% which is attributable to the higher prices of food, petroleum products, utilities, etc. Filipino customers turned lesser optimistic during the second quarter and the overall confidence level went negative as compared to the positive confidence index during 2017. The recent Consumer Expectation Survey (CES) showed the consumer confidence index (CI) declined to 10.2% after registering the highest 13.1% among the highest CI among consumers around the world.The country’s strong and stable communication sector has been cited as a key infrastructure industry that will help boost Philippine economic growth in the coming years. Telco sector was one of the major infrastructure industries – which also includes airports, power, road, and water which will help the economy to grow by 7% to 10% in the next 10 years. Filipinos being labelled as ‘text capital of the world’ have strong dependency to telco companies. Due to increasing use of social media and internet of things, citizens will always allocate a certain portion of their disposable income either to prepaid or postpaid load for connectivity and communication channel to their families, friends, and colleagues.